Fundamental Frequency and Regional Variation in Lifou French. (December 2022) - Torres, Catalina; Fletcher, Janet; Wigglesworth, Gillian
This study presents two experiments aimed at investigating tune-to-text alignment and pitch scaling in Lifou French, a variety spoken by bilingual speakers of French and Drehu. Descriptions of New Caledonian French have focussed on language use of European descendants or the variety spoken in the urban region, neglecting emergent varieties spoken by the indigenous population in rural areas, like the island Lifou. Due to the reduced inventory of pitch accents, dialectal variation in French intonation has proved to be difficult to detect, which has led to the assumption that French has a relatively homogeneous intonation system across its varieties. This study shows that fine-grained phonetic differences in speaking tempo and at the level of tonal alignment as well as in the scaling of AP-final peaks can be attributed to dialectal variation.